Elements of parametric design - Woodbury, Robert (Routledge, 2010)
What is parametric modeling? -- How designers use parameters : Conventional and parametric ; New skills ; New strategies -- Programming : Values ; Variables ; Expressions ; Statements ; Control statements ; Functions ; Types ; Objects, classes and methods ; Data structures, viz. lists ; conventions for this book ; It's more than writing code ; Parameter + Algorithm ; End-user programming -- The new Elephant House : Capturing design intent ; The torus ; Structure generator ; Frit generator -- Geometry : Vectors and points ; Lines in 2D ; Lines in 3D ; Planes ; Coordinate systems [equivalent] frames ; Geometrically significant vector bases ; Composing vector bases ; Intersections ; Curves ; Parametric surfaces -- Geometric gestures : Geometrical fluidity: White Magnolia Tower ; Designing with bits: Nanjing South Station ; Alternative design thinking -- Patterns for parametric design : The structure of design patterns ; Learning parametric modeling with patterns ; Working with design patterns ; Writing design patterns ; Clear names ; Controller ; Jig ; Increment ; Point collection ; Place holder ; Projection ; Reactor ; Reporter ; Selector ; Mapping ; Recursion ; Goal seeker -- Design space exploration : Introduction : Design space; Alternatives and variations ; Hysterical space ; Case study ; Representing the hysterical space ; Visualizing the hysterical space.